Socioeconomic and legal analysis of court fees structure and payment system in Ethiopia: Towards a policy-oriented approach - Mengistie, Belay Tizazu (Journal of Socioeconomics and Development, 2022)
Court fees in Ethiopia are governed by the Court Fees Regulation Number 177/1945. Although many things have changed over the past 67 years, none of the consecutive governments attempted to revise the court fee system. The user charge on judicial litigation (court fees), is justified for the existence of negative externalities that each user (litigant) generates to society. This is generated by the existence of incomplete markets, where the private benefits of litigation differ from social benefits. The charge has to match both benefits (private and social) and reach a social optimal equilibrium. The argument is that when private litigation costs are less than the social costs, there will be an inefficiently high level of litigation. Methodologically, a total of 44 legal professionals who have most frequent contact with the court and individuals undergoing trial were interviewed for operational purposes of the study... Key finding revealed that most respondents identified a problem with the existing court fee structure and payment system including controversies with respect to specified and unspecified claims. The new court fee will fill the gap that applied since 1945. So it should be amended in some respects according to the recommendations and steps which should be considered when passing an amended court fee regulation based on this proposal across the three level of federal courts. JEL Classification J33; K00; K41